Benefits realization management in the context of a national digital transformation initiative in English provider organizations. (20th December 2021) - Cresswell, Kathrin; Sheikh, Aziz; Franklin, Bryony Dean; Hinder, Susan; Nguyen, Hung The; Krasuska, Marta; Lane, Wendy; Mozaffar, Hajar; Mason, Kathy; Eason, Sally; Potts, Henry W W; Williams, Robin
Abstract: Background: The Global Digital Exemplar (GDE) Programme is a national initiative to promote digitally enabled transformation in English provider organizations. The Programme applied benefits realization management techniques to promote and demonstrate transformative outcomes. This work was part of an independent national evaluation of the GDE Programme. Aims: We explored how benefits realization management was approached and conceptualized in the GDE Programme. Methods: We conducted a series of 36 longitudinal case studies of provider organizations participating in the GDE Programme, 12 of which were in depth. Data collection included a combination of 628 interviews (with implementation staff in provider organizations, national programme management staff, and suppliers), 499 documents (of national and local implementation plans and lessons learned), and 190 nonparticipant observations (of national and local programme management meetings to develop insights into the broader context of benefits realization activities, tensions arising, and how these were negotiated). Data were coded drawing on a sociotechnical framework developed in related work and thematically analyzed, initially within and then across cases, with the help of NVivo 11 software. Results: Most stakeholders broadly agreed with the rationale of benefits realization in the GDE Programme to show due diligence that public money was appropriately spent, and to develop an evidence base supporting the value of digitally enabled transformation. Differing national and local reporting purposes, however, created tensions. Central requirements, for progress reporting and tracking high-level benefits, had limited perceived local value and were seen to impose an unnecessary burden on provider organizations. This was accentuated by the lack of harmonization of reporting requirements to different stakeholders (which differed in content and timing). There were tensions between the desire for early evidence of outcomes and the slow processes of infrastructural change (which created problems of attribution of benefits to causes as benefits emerged gradually and over long timeframes), and also between reporting immediately visible local changes and showing how these flowed through to high level organization wide benefits (eg, in terms of health outcomes or cost savings/return on investment). The attempt to fulfill these diverging agendas and informational needs within a single reporting tool had limited success. These difficulties were mitigated by efforts to simplify reporting requirements and to support targeted collection of key national outcome measures. Although progress was hampered by an initial lack of benefits realization expertise in provider organizations, some providers subsequently retained these skills for their own change management purposes. Conclusions: There is a need to recognize the limitations and cost of benefits realization management practices in the context of healthcare digitalization where benefits may materialize over long timeframes and in unanticipated ways. Although diverse stakeholder information needs may create tensions, prior agreement about rationales for collecting information and a targeted approach to tracking local and high-level benefits may enhance local relevance, reduce perceived reporting burdens, and improve acceptance/effectiveness. A single integrated reporting mechanism is unlikely to fulfill both national and local requirements.